2015
DOI: 10.1111/1911-3846.12168
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Country Evidence on the Importance of Auditor Choice to Corporate Debt Maturity

Abstract: We examine the importance of Big Four audits in reducing agency costs evident in corporate debt maturity worldwide. Analyzing a large sample of public firms from 42 countries reveals that the fraction of long-term debt in firms' capital structures rises with the presence of a Big Four auditor, suggesting that higher-quality audits substitute for short-term debt for monitoring purposes. In additional analyses, we find that the role that auditor choice plays in debt maturity is concentrated in firms from countri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 108 publications
1
44
1
Order By: Relevance
“…Knechel et al () found that the demand for audit quality appears to increase with size and financial leverage for the smallest Finish firms, who are allowed to use noncertified auditors. El Ghoul et al () analyzed samples from 42 countries and found that the level of debts with longer maturity in firms rises with the appointment of Big N auditors. Their result indicates that high‐quality audits substitute for short‐term lending for monitoring purposes.…”
Section: Determinants Of Auditor Choicementioning
confidence: 99%
See 2 more Smart Citations
“…Knechel et al () found that the demand for audit quality appears to increase with size and financial leverage for the smallest Finish firms, who are allowed to use noncertified auditors. El Ghoul et al () analyzed samples from 42 countries and found that the level of debts with longer maturity in firms rises with the appointment of Big N auditors. Their result indicates that high‐quality audits substitute for short‐term lending for monitoring purposes.…”
Section: Determinants Of Auditor Choicementioning
confidence: 99%
“…The risk of asymmetric information expands the concern of auditor choice to a broad range of capital providers other than the agency conflicts embedded in the firms' ownership structures. Auditor choice is of concern to debt holders, who also benefit from a high-quality audit, because debt covenants are written using accounting information (Chow, 1982;El Ghoul, Guedhami, Pittman, & Rizeanu, 2016;Hay & Davis, 2004;Knechel, Niemi, & Sundgren, 2008).…”
Section: Information Asymmetry Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…In this vein, Antoniou et al (2006) find that the average ratio of long-term debt to total debt is higher in France (59%) than in Germany (53%) and the United Kingdom (46%). El Ghoul et al (2015) and Zheng et al (2012) also report that, on average, French firms have longer debt maturities than many other European countries, such as Germany, Italy and the United Kingdom.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The variable DEBT_MATURITY_2 is a dummy variable that equals one if more than 50% of the firm's total debt is long-term and zero otherwise. 22 The variable DEBT_MATURITY_3 is calculated as the difference between a firm's total liabilities and current liabilities, divided by its total liabilities (El Ghoul et al, 2015). Table 9 shows that the coefficient on MLSD is negative and statistically significant at the 1% level in specifications (1) and (2).…”
Section: Alternative Dependent Variables and Regression Frameworkmentioning
confidence: 99%